(untitled) (University Heart Journal, 2015)
The choice of the surgical technique and quality of surgical repair determine the cardiac outcome of Tetralogy of Fallot(TOF) with anomalous coronary artery(ACA). On the other hand, the type of surgical reconstruction depends on the size of pulmonary annulus and the exact location of ACA in relation to pulmonary annulus.A unified repair strategy that limits and balance between postoperative residual pulmonary stenosis(PS) and pulmonary insufficiency (PI) after patch enlargement is critical for preservation of ventricular function with or without deliberate sacrifice of ACA In condition of inadvertent transaction or necessiate sacrefice of ACA during right ventricular outflow tract obstruction (RVOTO) repair needs urgent coronary artery bypass grafting (CABG) using left internal mamary artery(LIMA)/autologous venous conduit to prevent myocardial infarction. Palliative procedure in neonates is needed in conditions eg., anomalous coronaries, multiple ventricular septal defects(VSD), generalized critical illness, rehabilitation of small or distorted pulmonary artery (PA), prematurity and low birth weight etc.is followed by repair University Heart Journal Vol. 9, No. 2, July 2013; 112-118